2023
DOI: 10.1038/s41372-023-01655-y
|View full text |Cite
|
Sign up to set email alerts
|

NICU sensory experiences associated with positive outcomes: an integrative review of evidence from 2015–2020

Abstract: To inform changes to the Supporting and Enhancing NICU Sensory Experiences (SENSE) program, studies investigating sensory-based interventions in the NICU with preterm infants born ≤32 weeks were identified. Studies published between October 2015 to December 2020, and with outcomes related to infant development or parent well-being, were included in this integrative review. The systematic search used databases including MEDLINE, Cumulative Index to Nursing and Allied Health Literature, the Cochrane Library, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 147 publications
0
1
0
Order By: Relevance
“…Study findings were summarized qualitatively, with evidence related to each type of sensory intervention defined across PMA. Fifty-seven new articles on sensory-based interventions (auditory, vestibular, visual, kinesthetic, and olfactory/gustatory) were identified that were used to improve outcomes for preterm infants and their parents in the NICU [ 25 ].…”
Section: Methodsmentioning
confidence: 99%
“…Study findings were summarized qualitatively, with evidence related to each type of sensory intervention defined across PMA. Fifty-seven new articles on sensory-based interventions (auditory, vestibular, visual, kinesthetic, and olfactory/gustatory) were identified that were used to improve outcomes for preterm infants and their parents in the NICU [ 25 ].…”
Section: Methodsmentioning
confidence: 99%